2014
DOI: 10.3233/jvr-140689
|View full text |Cite
|
Sign up to set email alerts
|

Transition of culturally and linguistically diverse youth with disabilities: Challenges and opportunities

Abstract: Youth with disabilities who come from culturally and linguistically diverse (CLD) backgrounds have markedly poorer adult life transition outcomes compared to White youth with disabilities. This article explores the literature on transition outcomes of youth with disabilities who are White, Hispanic, and African American and argues that high numbers of CLD youth with disabilities are likely to be on the caseloads of transition services personnel now and in the future. Statistics from the U.S Census bureau are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…Schools can also invite some families of youth with disabilities who have gone through the transition planning process to share their experiences in these sessions. Giving families of students with disabilities opportunities to network and learn from each other is crucial, especially for diverse families (Greene, 2011), because they feel comfortable connecting with families who speak the same language and are from the same culture (Kim et al, 2007; Lo, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schools can also invite some families of youth with disabilities who have gone through the transition planning process to share their experiences in these sessions. Giving families of students with disabilities opportunities to network and learn from each other is crucial, especially for diverse families (Greene, 2011), because they feel comfortable connecting with families who speak the same language and are from the same culture (Kim et al, 2007; Lo, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Gothberg and her colleagues (2019) surveyed 90 school districts in the United States about whether or not they had implemented any of the 11 research-based practices (RBPs) for transition planning with diverse youth with disabilities and their families that were identified by Greene (2011). They found that most school districts did not fully implement any of the RBPs.…”
mentioning
confidence: 99%
“…Numerous published articles have discussed a lack of quality teacher training at the university, state, and local levels for preparing special educators for their roles and responsibilities in transitioning youth with disabilities from school to adult life (see Benetiz, Morningstar, & Frey, 2009; Flannery, Lombardi, & McGrath Kato, 2015; Kohler & Greene, 2004). Greene (2011) argued that even less time is dedicated in special education teacher training programs to the topic of transition of CLD youth with disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…These include (a) teachers who have higher expectations for White and Asian students, and lower expectations of Latino, Black, and Native American students (Cherng, 2015; Downey & Ainsworth-Darnell, 2002; Tenenbaum & Ruck, 2007); (b) educators who lack or have a limited understanding of the culture of various CLD families of the students they are teaching (Pewewardy & Fitzpatrick, 2009; Robinson, 2016; Rueda, Monzo, Shapiro, Gomez, & Blacher, 2005); (c) racial, cultural stereotypes, and biases in school personnel toward CLD families as well as school personnel consciously or unconsciously viewing culture as a liability (Brandon & Brown, 2007; Geenen, Powers, Lopez Vasquez, & Bersani, 2003; Gil-Kashiwabara, Hogansen, Geenen, Powers, & Powers, 2007; Harry, 2008; Landmark, Zhang, & Montoya, 2007). Additional school structural inequalities toward CLD families of youth with disabilities were identified by Greene (2011). These included special educators’ lack of acknowledgment of CLD families’ hopes and dreams for their children’s futures (Brandon & Brown, 2007; Lai & Ishiyama, 2004; Landmark et al, 2007; Pewewardy & Fitzpatrick, 2009; Rueda et al, 2005), special educators’ lack of sensitivity to CLD family immigration issues and limited language proficiency, and parents of CLD youth with disabilities reporting feeling intimidated when interacting with school personnel and feeling that their participation in the transition planning process was cursory (Landmark, Roberts, & Zhang, 2013; Leake & Boone, 2007).…”
Section: School Structural Inequalities Affecting the Transition Of Cmentioning
confidence: 99%
See 1 more Smart Citation